iPARTY study: Increasing pre-exposure prophylaxis access and reach via telehealth for young men who have sex with men in Singapore 2022–2023 - Pei Hua Lee; Justin Y Lim; P Arun Kumar; Zhi Hui Tan; Rayen Bing Hui Tan; Chiaw Yee Choy; Rayner Kay Jin Tan; Martin TW Chio; Chen Seong Wong (Annals, Academy of Medicine, Singapore)
Introduction: Although pre-exposure prophylaxis (PrEP) has been available in Singapore since 2016, its uptake among gay, bisexual and other men-who-have-sex-with-men (GBMSM) is low. The iPARTY study was established to evaluate the acceptability and feasibility of PrEP and a PrEP teleconsultation service for young GBMSM aged 18 to 29 years. Method: A total of 53 young GBMSM were enrolled in the iPARTY study. They had a total of 5 in-person consultations and teleconsultations, at 12-week intervals. Laboratory tests and quarterly baseline surveys were performed to assess PrEP adherence, sexual behaviour, and incidence of human immunodeficiency virus (HIV) and other sexually transmitted infections (STIs). Results: Thirty-five participants completed the entire 12-month follow-up. Most participants had positive experiences with PrEP teleconsultations. There was a statistically significant fall in participants’ aggregate Patient Health Questionnaire-9 scores throughout the study. Self-reported PrEP adherence decreased over the course of the study, denoting improved mental health. Although self-reported condom use for anal intercourse and participants’ risk perception of HIV decreased after PrEP adoption, there was no statistically significant increase in STI incidence. Conclusion: This pilot project has shown that PrEP services provide an opportunity for YMSM to access sexual health testing, treatment and counselling, and may even have tangible benefits on the mental health of this population. Teleconsultation is shown to be a suitable platform for the delivery of such services. Collaborative initiatives are crucial to further enhance the affordability and accessibility of PrEP in Singapore, and to improve patient adherence.